Stiffness and echogenicity: Development of a stiffness-echogenicity matrix for clinical problem solving - Antonio Stecco; Carmelo Pirri; Raffaele De Caro; Preeti Raghavan (PAGEPress Publications, 2019)
The assessment of soft tissue stiffness is important to evaluate many neuromusculoskeletal conditions. Several tools have been proposed for the assessment of stiffness, but ultrasonography appears to be most practical. The reflection of ultrasound waves as it travels through tissue enables assessment of tissue echogenicity, which is influenced by the characteristics of the sound wave as well as the characteristics of the tissue through which it passes, such as the amount of fat and fibrous tissue. However, tissue stiffness is not directly proportional to its echogenicity. Hence evaluation of echogenicity, as a stand-alone technique, is inadequate to describe its mechanical properties. The aim of this manuscript is to present a method of combining echogenicity evaluation by ultrasound and stiffness evaluation by palpation to better describe the mechanical properties of muscle using a stiffness-echogenicity matrix.